Open and Notorious: Adverse Possession and Immigration Reform - Timothy J. Lukes; Minh T. Hoang (Washington University Journal of Law & Policy, 2008)
We suggest that there are reasons to support the patriation of undocumented immigrants without invoking sentimentality, generosity or amnesty, all of which tend to elicit commensurate sanctions and indignance. Instead, we want to confront directly the seemingly airtight presumption of illegality. We will depend in our argument upon a concept in property law. The concept is adverse possession, and in some form or other, it exists in most legal systems throughout the world. Simply put, adverse possession allows a proprietary claim to individuals who have occupied property that is not initially theirs. We will show how the concept of adverse possession can assist immigration progressives to face the legality issue rather than sidestep it, in so doing strengthen the argument for a humane and rational immigration policy.
Keywords: Adverse possession – policy; Immigration reform; Foreign labor; Immigration policy; Immigration – politics; United States; Alien labour; California; States